If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2(2x + 3) = 3(x + 7) Reorder the terms: 6 + -2(3 + 2x) = 3(x + 7) 6 + (3 * -2 + 2x * -2) = 3(x + 7) 6 + (-6 + -4x) = 3(x + 7) Combine like terms: 6 + -6 = 0 0 + -4x = 3(x + 7) -4x = 3(x + 7) Reorder the terms: -4x = 3(7 + x) -4x = (7 * 3 + x * 3) -4x = (21 + 3x) Solving -4x = 21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -4x + -3x = 21 + 3x + -3x Combine like terms: -4x + -3x = -7x -7x = 21 + 3x + -3x Combine like terms: 3x + -3x = 0 -7x = 21 + 0 -7x = 21 Divide each side by '-7'. x = -3 Simplifying x = -3
| 40=(x+3)(x+3) | | 17y-18=15y-13 | | y=-0.5+12 | | -8=15+z | | 3x+2x=31 | | 2x^3+3x^2+x+2=0 | | 2w-3x-y+5w+17x-8y= | | 2x+7x=400 | | 3x-8=-1-5x | | 6x-3y+12w-6y-5w+8x= | | -11(0)+4(0-3)+6(0)=4(0)-12 | | 4w+5y+12x+2x-14y+4w= | | 4w+3x+13y+3w+11x-4y= | | 4x+2x=200 | | 2X-7=-5X+14 | | Mx^2+2mx+m-1=0 | | 11x^2+13x+9=11 | | 2.50r+3.50=16 | | 10x-9x=3 | | 5x-14=-54 | | x^9=7 | | 9T+9T= | | 8x+21=5x+90 | | -15=5-q | | 1+x=-4 | | 7(3x-1)=3(2x+5) | | 4-5x=x-3 | | 7.65x+61.2=122.4 | | 0.15d+0.07(1000-d)=130 | | -2+2k+3=-3 | | 4x+28=2x | | 8-3x+7x=15-3x |